FAKTOR YANG MEMPENGARUHI INDEKS HARGA SAHAM PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Widnyani, Ni Made; Ayuni, Ni Made Sri; Budiasni, Ni Wayan Novi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.07.TAHUN.2022, 2022)
This study was conducted to test how the effect of independent variables (Inflation, Exchange Rate and Interest Rate) on dependent variables (Stock Prices) on Telecommunications Sector companies listed on the Indonesia Stock Exchange during the period January 2018 to March 2021. This research is a type of quantitative because it refers to the calculation and research of secondary data in the form of numbers. By applying Documentation Studies and Literature Research as data collection techniques, purposive sampling techniques to obtain representative samples in accordance with the specified criteria, as well as applying the Classic Assumption Test of Multiple Regression Models and Hypothetical Testing as data analysis techniques in this study. Therefore, the following results are obtained: Inflation has a positive and significant effect on the Stock Price, interest rate has a negative and significant effect on the Stock Price, Rupiah Exchange Rate has no influence on the Stock Price, and based on the analysis of the Coefficient of Determination (R 2 ) inflation, interest rate and rupiah exchange rate is able to explain the variable bound by 56.9% , while 43.1% is influenced by other variables outside the regression model.